Mountaineering : The Freedom of the Hills - Editors Graydon, Don and Hanson, Kurt (Shrewsbury Swan Hill, 1997)
Written for both beginners and advanced climbers, this revised and updated edition reflects current techniques and new and improved equipment. Four sections cover climbing and outdoor fundamentals; rock, snow, ice and alpine climbing; emergency prevention and response; and the mountain environment
Include Illustration and Index
Keywords: Mountaineering -- Rock climbing -- Snow and ice climbing